Study Behaviour of Prabowo Subianto’s Leadership as the President of Indonesia - Mazda, Chadziqatun Najilatil; Nurhayati , Ema; Putra, Rivaldi Ananda Dwi (Southeast Asia Development Research, 2025)
Based on Article 1, Paragraph 1 of the 1945 Constitution, Indonesia is a unitary state in the form of a Republic. As a republic, Indonesia is led by a president. On March 20, 2024, the Indonesian Election Commission (KPU) officially announced Prabowo Subianto’s landslide victory. In carrying out duties as president, leadership characteristics are needed that can influence, direct, and evaluate performance in achieving the goals set. By studying behaviour, one can find out the background, experience, and knowledge of a person, which ultimately form a person’s character or behaviour in acting. This article aims to conduct a study of the behaviour of Prabowo Subianto as the president of Indonesia and its impact on development policy. This study uses a qualitative method with a focus on text and analysis of the characteristics of Prabowo Subianto’s leadership behaviour and its impact on development policy. The results show that Prabowo Subianto’s leadership is heavily influenced by his background as a former member of the Special Forces Command (Kopassus), which shaped his firm and disciplined leadership characteristics. Study behaviour reveals several key aspects of Prabowo Subianto as the president of Indonesia, including being a firm leader, one who is close to the people, familiar with religious and political figures, and actively involved in direct inspections of field activities. Several efforts and development sectors are highlighted in strengthening Indonesia’s development and its impact on development policy through industrialisation, human resources, technology, infrastructure, and education.